The Role of Social Movements in the Recognition of Gender Violence as a Violation of Human Rights: From Legal Reform to the Language of Rights - Calvo García, Manuel (The Age of Human Rights Journal, 2016)
The history of rights shows that the struggle for the recognition of women’s rights was difficult enough and the recognition of the right of women to a life without gender violence has been even more difficult. With a perspective based in a socio-legal and critical approach, this article defends that the recognition of the right of women to a life free of gender violence must be seen as a conquest of the feminist movement and women’s organizations.  It was the struggle of the feminist movement which provided the catalyst for the recognition of women’s rights and the specific right of women to a life free of gender violence and to protection against such violence. But not only the recognition, also the praxis of the right of women to a life free of gender violence is important.  The right of women to a life free from gender-based violence cannot be fully realized without the implementation of this right at the international and the local level. The implementation of rights and the existence of social movements involved with the right to a life free from gender violence is decisive to transforms the demands for protection from violence and its eradication to be see not as a question of mercy, but as a question of justice; and putting the individual experiences of gender violence victims within a wider framework from which the abuse can be considered as a social problem.